Secretion and Endocytosis in Pollen Tubes: Models of Tip Growth in the Spot Light - Grebnev, Gleb; Ntefidou, Maria; Kost, Benedikt (Frontiers in Plant Science, 2017)
Pollen tube tip growth is a widely used model ideally suited to study cellular processes underlying polarized cell expansion. Local secretion supplying material for plasma membrane and cell wall extension is essential for this process. Cell wall biogenesis requires fusion of secretory vesicles with the PM at an about 10x higher rate than plasma membrane extension. Excess material is therefore incorporated into the plasma membrane, which needs to be reinternalized through endocytosis. The classical model of tip growth proposes that exocytosis occurs at the apex and that newly incorporated plasma membrane material is transported to adjacent lateral regions, where excess material is endocytically recycled. This model was recently challenged based on studies indicating that lateral exocytosis may be balanced by apical endocytosis. This review provides an overview of published data pertaining to exocytosis, endocytosis and vesicular trafficking in pollen tubes. Its key aim is to present classical and alternative models of tip growth in the light of available experimental data. By necessity, the review focusses on pollen tubes of angiosperm models (N. tabacum, Arabidopsis, L. longiflorum), which have been studied far more extensively and grow much faster than structurally strikingly different gymnosperm pollen tubes. Only major transport pathways are considered, which substantially contribute to the mass-flow of membrane material at the pollen tube tip. Growth oscillation, which may be displayed in particular by fast-growing pollen tubes, are not discussed as their influence on the spatial organization of apical membrane traffic is not understood.